Quality Of Learning Outcomes Using The Blended Learning By Students Of The History Education Study Program In The New Normal Era - Sukardi, Sukardi; Edi Harapan (International journal of technology and education research, 2023)
The study's objective is to characterize and assess how the blended learning model affects the caliber of historical learning results in the contemporary day. This research uses quantitative methods with a simple correlation approach. The research location was in the History Education Study Program FKIP PGRI Palembang University, with a sample of 114 active students who were taken randomly. Data was collected using observation, documentation, and questionnaires. According to the study's findings, the quality of learning outcomes was significantly impacted by the blended learning pattern in the new normal era by 0.325. It was concluded that the quality of learning outcomes for students of the History Education Study Program, FKIP University of Palembang, was successful after implementing the mixed learning pattern in the new normal era. In order to improve the caliber of learning outcomes, it is advised that the History Education Study Program continue to combine online and offline learning methods in the new normal period. It has been demonstrated that when the blended learning pattern is applied as best it can, the caliber of student learning outcomes rises.